Comparative Therapeutic Efficacy Of Griseofulvin And Fluconazole In Canine Dermatophytosis - Narang, Asmita; Arora, Niddhi; Rajora, V.S.; Krishan, Gopal; Singh, J.L.; Mrigesh , Meena (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A clinico-therapeutic study was conducted on 12 dermatophytosed dogs brought to TVCC, Pantnagar. Two groups of 6 dogs each were formed. Efficacy of oral Griseofulvin and fluconazole in dermatophytosis was evaluated. The clinical examination of the dogs was followed every 7 days till complete cure and hemato-biochemical evaluation before and after treatment was performed. Griseofulvin was found superior to fluconazole in treatment of canine dermatophytosis on the basis of disappearance of clinical manifestations, recovery rate post treatment, hematological and biochemical profiles. Moreover, fluconazole increased the activity of ALT that indicated hepatocellular damage.